EVALUATION DES PRATIQUES SUR LE LAVAGE DES MAINS CHEZ LES ELEVES DES ECOLES PRIMAIRES DE LA SOUS DIVISION EDUCATIONNELLE DE KALIMA 2021-2022 - Bernoulli, Amuri Lukamba; Daphrose, Kamulume Kakasi; Pierrette, Moza Mbela; Paulin, Kalume Isimbia; Samuel, Mwamba Ilunga (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
Our study focused on the evaluation of handwashing practices among primary school students in the Kalima educational subdivision. The following observations emerged: The overall level of handwashing was good , 7 out of 10 students (73.2 ) had good handwashing practices; 8 had washed their hands on the day of the survey , 51.0 with soap and water and 59.9 for 30 seconds to 1 minute ; Students wash their hands 70 to 3 before meals. Proper handwashing helps students prevent illnesses and stay healthy.